CONTRADICTIONS IN THE LEGAL STATUS OF STATE-OWNED ENTERPRISE (BUMN) SUBSIDIARIES IN THE PARENT HOLDING COMPANY - Yuda Tri Pagrelia; Ariawan Gunadi (Transpublika Publisher, 2024)
The creation of a cluster-based holding company in a State-Owned Enterprise (BUMN) related to core business fields requires careful attention and precise implementation. One must be cautious because issues regarding legal procedures and the legal status of BUMN can still arise. This writing discusses the legal relationship between BUMN Persero and its subsidiaries based on the theory and doctrine of limited liability companies, as well as the contradictory legal status of BUMN subsidiaries within the parent holding company. The research method used in this writing is normative legal research. The findings demonstrate that the piercing the corporate veil doctrine can be employed in terms of evidence, where control of subsidiaries must be exercised by the holding company. Legal responsibility is applicable not only to companies, but also to shareholders as specified in Article 3 paragraph (2) of Law Number 40 of 2007 on Limited Liability Companies (UUPT). Once BUMNs become subsidiaries in a holding company, their status as BUMNs, whether BUMN Perum or Persero, changes since their shares are now sourced from the holding company instead of the state. Therefore, BUMNs that become subsidiaries no longer possess legal standing or status as BUMNs, and the state assumes authority over aspects of control concerning BUMNs that have become subsidiaries of the holding company. This authority is indirectly held by the state via the parent/holding company, which represents the government in terms of share ownership, with the majority of shares originating from subsidiaries.